Fructose-induced severe hypertriglyceridemia and diabetes mellitus: a cautionary tale - Ana Dugic (Bioscientifica, 2021)
Drinking fruit juice is an increasingly popular health trend, as it is widely perceived as a source of vitamins and nutrients. However, high fructose load in fruit beverages can have harmful metabolic effects. When consumed in high amounts, fructose is linked with hypertriglyceridemia, fatty liver and insulin resistance. We present an unusual case of a patient with severe asymptomatic hypertriglyceridemia (triglycerides of 9182 mg/dL) and newly diagnosed type 2 diabetes mellitus, who reported a daily intake of 15 L of fruit juice over several weeks before presentation. The patient was referred to our emergency department with blood glucose of 527 mg/dL and glycated hemoglobin (HbA1c) of 17.3%. Interestingly, features of diabetic ketoacidosis or hyperosmolar hyperglycemic state were absent. The patient was overweight with an otherwise unremarkable physical exam. Lipase levels, liver function tests and inflammatory markers were closely monitored and remained unremarkable. The initial therapeutic approach included i.v. volume resuscitation, insulin and heparin. Additionally, plasmapheresis was performed to prevent potentially fatal complications of hypertriglyceridemia. The patient was counseled on balanced nutrition and detrimental effects of fruit beverages. He was discharged home 6 days after admission. At a 2-week follow-up visit, his triglyceride level was 419 mg/dL, total cholesterol was 221 mg/dL and HbA1c was 12.7%. The present case highlights the role of fructose overconsumption as a contributory factor for severe hypertriglyceridemia in a patient with newly diagnosed diabetes. We discuss metabolic effects of uncontrolled fructose ingestion, as well as the interplay of primary and secondary factors, in the pathogenesis of hypertriglyceridemia accompanied by diabetes.